Post-9/11 Evolution of the National Guard's Role in Homeland Defense - Raney, Matthew A. (2007)
The United States strategy to defend the homeland has been evolving since the terrorist attacks of September 11, 2001. Not only have the terms used to describe this strategy changed, so have the roles and responsibilities of many of the institutions tasked with executing the strategy. The Department of Homeland Security and Northern Command (NORTHCOM) are two examples of a radical organizational shift in strategy. In other instances, the implementation of change has been somewhat slower, such as in the case of the National Guard. One of the most notable changes in the National Guard has been its shift from a Cold War era strategic reserve to its current role as an operational reserve. But there have been other changes in the manner in which the National Guard operates. The purpose of this paper is to briefly examine some of the post-9/11 recommendations to increase, enhance or change the National Guard's role in homeland defense and civil support, to review steps actually taken by the National Guard to improve its homeland defense/civil support capabilities, and to illustrate the disparity between what the experts have said should be done and what the National Guard has actually done.